The radiological perspective of juvenile nasopharyngeal angiofibroma: A case report - Kaleb Taylor, MS; Marco DiBlasi, BA; Erik Pedersen, MD; Nastaran Shahsavari, MD (Radiology Case Reports)
Juvenile nasopharyngeal angiofibroma (JNA) is a rare, locally aggressive, highly vascularized benign tumor classically found in males from 13 to 20 years old. The most common clinical presentations are recurrent epistaxis and nasal congestion. Imaging plays a significant role in differentiating and determining the extension of nasopharyngeal lesions. The case below highlights a 15-year-old male that presented with nasal congestion and recurrent epistaxis, who underwent nasal endoscopy and ablation. Persisting symptoms led to further evaluation by computed tomography and magnetic resonance imaging of the head; thus, the patient was diagnosed with JNA. Subsequently, the patient underwent angiographic embolization of the maxillary artery branches and eventually, endoscopic tumor resection. The presenting case is an example for physicians that might encounter an unsuspecting case of JNA to expedite diagnosis and care.